If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + -1) + -3(2 + -1x) + 4(1 + -1x) = 0 Reorder the terms: 2(-1 + x) + -3(2 + -1x) + 4(1 + -1x) = 0 (-1 * 2 + x * 2) + -3(2 + -1x) + 4(1 + -1x) = 0 (-2 + 2x) + -3(2 + -1x) + 4(1 + -1x) = 0 -2 + 2x + (2 * -3 + -1x * -3) + 4(1 + -1x) = 0 -2 + 2x + (-6 + 3x) + 4(1 + -1x) = 0 -2 + 2x + -6 + 3x + (1 * 4 + -1x * 4) = 0 -2 + 2x + -6 + 3x + (4 + -4x) = 0 Reorder the terms: -2 + -6 + 4 + 2x + 3x + -4x = 0 Combine like terms: -2 + -6 = -8 -8 + 4 + 2x + 3x + -4x = 0 Combine like terms: -8 + 4 = -4 -4 + 2x + 3x + -4x = 0 Combine like terms: 2x + 3x = 5x -4 + 5x + -4x = 0 Combine like terms: 5x + -4x = 1x -4 + 1x = 0 Solving -4 + 1x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + 1x = 0 + 4 Combine like terms: -4 + 4 = 0 0 + 1x = 0 + 4 1x = 0 + 4 Combine like terms: 0 + 4 = 4 1x = 4 Divide each side by '1'. x = 4 Simplifying x = 4
| -23-4x=9-8x | | -134-7x=8x+16 | | -5(k+5)+5k= | | 5(b-4)+25= | | 0=3(2-3x)-7(x-3) | | 10+2(4y+3)= | | 3x-2(12-x)=4(2x-3)+3(x+1) | | 6-5c=-14 | | 6(1-x)+4=3(2-x)-4 | | 4x+10=90-6 | | 40-2(x+1)=90 | | 4k+6=6k-2 | | 6(2x+1)+7=9x+1 | | 6x+9=-119-10x | | 3(7x-1)+8(3-2x)=1 | | -2*5= | | 5(2x+3)-3(x+1)=5 | | 8(x-2)-2(2x-1)=2x+1 | | -2(5r+3)= | | 5a+30b=25 | | 5(3x-4)=8x+1 | | 6a-4=8 | | 3(10a)= | | 2x-3(2-x)=4 | | 4(x+3)-2=2 | | 3(x+1)+2(2x+7)=3 | | 5(f-12)=9+5f | | 6x+y-8x+y= | | 3(2x+5)+5(x-1)=-1 | | 7(x-1)-2(x-2)=3 | | 2(3x+8)-3(x-2)=25 | | 6x-5(4x+13)=33 |